EVALUASI PROGRAM PEMBELAJARAN PEKERJAAN DASAR TEKNIK OTOMOTIF KELAS X TKRO DI SMK NEGERI 1 SEDAYU - Zhafran Anas; Agus Budiman (Universitas Negeri Yogyakarta, 2020)
This research is to find out the Automotive Engineering Basic Work learning program at SMK Negeri 1 Sedayu focused on: context: learning planning; input: teacher, students, and infrastructure; process: media, methods, learning resources, and learning steps; product: student learning outcomes. Includes descriptive CIPP research models (context, input, process, product) evaluation. The results of the study note that the learning program Basic Automotive Engineering Work in SMK Negeri 1 Sedayu in terms of: context: the learning objectives of the PDTO learning program are in accordance with the 2013 Curriculum and not all basic competencies can be conveyed to students; input: PDTO teachers are undergraduate (S1) majoring in Mechanical Engineering Education and have educator certification, student motivation is quite good (46.296%), good classroom facilities and infrastructure (63.634%), and PDTO practice tools are very good (86.318%); process: the use of learning media is quite good (35.185%), the use of learning media is quite good (37.963%), the use of learning resources is quite good (37.963%), and the implementation of learning steps is very good (100%); product: the percentage of students completeness 41.667% and 54.630%.